온라인기반 스마트워크(Smart Work)가 사회자본과 개인 성과에 미치는 영향 - 양윤서(Yang, Yoonseo); 송재민(Song, Jaemin) (국토계획, 2021)
본 연구는 「7차 여성관리자 패널조사」 자료를 활용하여 스마트워크가 사회자본에 미치는 영향과 개인성과에 미치는 영향을 구조방정식을 통해 실증 분석한다. 제Ⅱ장에서는 사회자본 이론 및 스마트워크와 사회자본 관련 선행연구 검토를 통해본 연구의 필요성과 차별성을 확립한다. 그리고 제Ⅲ장에서는 본연구의 분석자료를 제시하고 변수구성, 연구가설과 분석모형에관한 분석 틀을 구축한다. 제Ⅳ장에서는 제Ⅲ장에서 구축한 분석틀을 바탕으로 확인적 요인분석, 구조방정식 모형 분석, 총효과및 간접효과를 분석하여 그 결과를 해석한다. 마지막으로 제Ⅴ장에서 결론을 맺으며 시사점을 도출한다. Due to the recent COVID-19 pandemic, social and academic interest in smart work, represented by telecommuting, is growing. Smart work is expected to replace the current face-to-face working style in the near future. However, there is a limited number of studies investigating its impact on society. Against this backdrop, the effects of smart work on social capital and individual performance have been analyzed using a structural equation model (SEM) with data from 「2018 Korean Women Manager Panel」, which includes 2,904 respondents. The key findings are as follows: First, the level of social capital of remote workers is higher than that of full-time workers. Second, social capital is positively associated with both job satisfaction and performance. Third, although smart work is negatively associated with wages, it is positively associated with job satisfaction and performance given its combined effects, both direct and indirect effects through social capital. In conclusion, contrary to common concerns, the result from this study demonstrates that smart work does not necessarily have negative impacts on social capital and performance, except for wages, than the traditional face-to-face working style. KCI Citation Count: 0